Mercury in fish and sediment of Purus River, Acre State, Amazon - CASTRO, Nathália Santos Serrão de (Universidade Federal do Pará, 2017)
Core subject: To quantify the Hg content of sediment and fish collected along the Purus River (Acre State, Amazon) in order to identify if those samples could be a potential route of Hg exposure to the population of Manoel Urbano (a riverside community). Methods: The total mercury (THg) was quantified using the Cold Vapor Atomic Absorption technique. Results: We collected 06 samples of sediment and 264 samples of fish. The Hg in sediments ranged between 0.038 and 0.065 µg.g–1.The results indicate that sediment is in agreement with “uncontaminated” Amazonian rivers. The carnivorous species presented the highest level of Hg on muscle (mean 0.927 µg/g–1), followed by piscivorous (mean 0.873 µg.g–1), planktophagus (mean 0.566 µg.g–1), omnivorous (mean 0.533 µg.g–1) and detritivorous (mean 0.176 µg/g–1). Fourty four percent (44%) of the total species collected presented mean levels of THg on muscle, a percentage greater than the threshold recommended by WHO. Conclusion: Some species may be a route for Hg exposure. The sediment is within the normality. The authors suggest that other factors, such as culture and society, should be considered for future researches in order to promote the population healths.